2022
DOI: 10.1177/15385744221098810
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Enhanced Recovery for Open Abdominal Aortic Aneurysm Surgery

Abstract: Introduction: Open abdominal aortic aneurysm (AAA) surgery is associated with significant morbidity, mortality and high length of stay (LOS). Enhanced recovery is now commonplace and has been shown to decrease these in other non-vascular surgery settings. This systematic review and meta-analysis aimed to assess the benefits of enhanced recovery (ERAS) in aortic surgery. Method: Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines were used to undertake a systematic review via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…This study showed encouraging results, with decreased postoperative assisted mechanical ventilation, fewer medical complications and faster recovery of gastrointestinal function. A recently published meta-analysis found benefits of ERAS in OAS in terms of hospital stay and postoperative complications, while no difference was found in 30-day mortality [78].…”
Section: Enhanced Recovery Pathwaysmentioning
confidence: 93%
See 2 more Smart Citations
“…This study showed encouraging results, with decreased postoperative assisted mechanical ventilation, fewer medical complications and faster recovery of gastrointestinal function. A recently published meta-analysis found benefits of ERAS in OAS in terms of hospital stay and postoperative complications, while no difference was found in 30-day mortality [78].…”
Section: Enhanced Recovery Pathwaysmentioning
confidence: 93%
“…There is no available standardized ERAS protocol, but it is acknowledged that the positive influence on outcomes mainly depends on a combination of measures, with the isolated effect of individual elements being less important [79]. Integral components that should be considered and protocoled in all enhanced recovery pathways are fasting and carbohydrate loading, multimodal analgesia, prevention of postoperative nausea and vomiting, patient warming, anaesthetic protocols, postoperative fluid management, catheter/drain removal, early mobilization, and chest physiotherapy [20,78].…”
Section: Enhanced Recovery Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing body of evidence supporting the safety and efficacy of the enhanced recovery after surgery concept for various procedures. The most recent meta-analysis showing beneficial effects are in thyroid surgery [8 ▪ ], aortic aneurysm surgery [9 ▪ ] and pediatric surgery [10 ▪ ] all supporting its benefits in shortening hospital stay and improving patients’ satisfaction.…”
Section: Enhanced Recovery After Surgery Pathwaysmentioning
confidence: 99%
“…ERAS protocols must strike a delicate balance between delivering optimal care quality and reducing healthcare costs [10]. Consequently, the primary objectives include diminishing POC [11][12][13][14], reducing lengths of stay (LOS) [11][12][13][14][15][16][17], alleviating postoperative pain, and facilitating the swift return to normal physiological function. This approach has demonstrated its efficacy in enhancing the patients' quality of life [18] and satisfaction [19] during the perioperative period.…”
Section: Introductionmentioning
confidence: 99%